Magnetic resonance imaging findings in a patient with cryopyrin-associated periodic syndrome: A rare hereditary multi-system inflammatory disorder. Issue 6 (December 2019) - Behringer, Jessica; Ryan, Maura; Miller, Michael; Jaju, Alok
Cryopyrin-associated periodic syndrome is a hereditary inflammatory disorder encompassing a wide spectrum of clinical phenotypes. This disorder has been associated with mutation of the NLRP3 gene coding for cryopyrin, which leads to overproduction of interleukin-1. The condition causes relapsing bouts of inflammation involving multiple organ systems, including the central nervous system, and, if untreated, can lead to long-term debilitating effects. A literature review revealed only a few brief descriptions of magnetic resonance imaging findings in cryopyrin-associated periodic syndrome patients. We describe serial magnetic resonance imaging findings in an 11-year-old female with clinically diagnosed cryopyrin-associated periodic syndrome who presented with intermittent headaches, progressive sensorineural hearing loss, fevers, and abdominal pain. The magnetic resonance imaging showed progressively worsening low T2 signal in the cochlea, cochlear enhancement, and leptomeningeal enhancement. We also describe some previously unreported findings in this syndrome, including cranial nerve and cauda equina enhancement.